Location Based Service Daerah Rawan Kecelakaan Dan Tindak Kriminalitas Menggunakan Metode Agile Up: Agile-Based Location Service for Accident and Crime-Prone Areas - Palilingan, Kenneth Y.R.; Lengkong, Salvius; Salaki, Reynaldo (Jurnal Teknik Informatika, 2024)
In the era of rapid development of information technology, every group of people from various ages really needs digital media connected to the internet so that people can provide and receive information quickly in all areas of life. On the other hand, the number of traffic accidents and crimes in the city of Manado is still relatively high, requiring every community to increase awareness and vigilance so as not to become victims. One effort that can be made is to utilize information technology to provide information to the public or newcomers about the location or points of areas prone to traffic accidents and crimes in the city of Manado Based on Location (Location Based Service) and this data can be updated in real time, Location Based Service is a technology that uses geographic data and information to provide services or information to users. That is the purpose of this study, namely to Analyze and design the Location Based Service Application for areas prone to traffic accidents and crimes in the city of Manado Using the Agile UP Method